The Traditional Uses, Phytochemistry and Pharmacology of Sarcandra glabra (Thunb.) Nakai, a Chinese Herb With Potential for Development: Review - Zeng, Yuanlian; Liu, Junyu; Zhang, Qiang; Qin, Xuhua; Li, Zulun; Sun, Guojuan; Jin, Shenrui (Frontiers in Pharmacology, 2021)
Sarcandra glabra (Thunb.) Nakai is a folk medicine with a long history in China, which has been applied to treat sore throat, abscess, even tumor and so on. Meanwhile, it is also used as tea in some areas . At present, more than 200 chemical compounds have been isolated and identified from it, such as, sesquiterpenes, flavonoids, phenolic acids, coumarins and so on. Pharmacological studies have already confirmed that the extracts of S. glabra have many effects, such as antibacterial, antiviral, anti-inflammatory, anti-tumor, and anti-thrombocytopenia, especially the effects of anti-tumor and anti-thrombocytopenia are confirmed in clinic. Therefore, this paper systematically summarized the traditional uses, botany, phytochemistry, pharmacology, and toxicity of S. glabra, in order to provide a beneficial reference of its further research.